NPedDesk Desktop Application for Informatics Control of an Infant Neurodevelopment Screening Program - Santos-Febles, Elsa; Gaya-Vázquez, J A; Pérez-Abalo, M C; Flores-Contreras, A P; Pérez-Guerra, M A (Revista Mexicana de Ingenieria Biomedica, 2012)
Screening programs are very important to early detection and diagnostic/intervention of a certain disease. A management of this information allows a correct follow up and also facilitates the further estimation of the typical parameters for screening effectiveness. NPedDesk application allows us to collect, organize and process the information that is generated in this type of programs when is based in the use of NPed test (neurodevelopmental delay screening test among infants and young children from 0-5 years old).The software was developed using visual programming tools: Microsoft Visual Studio Professional Edition 2008 version, C# language programming, Database engine Microsoft Access. NPedDesk is easy to used and ensure data security and robustness.